A critical review on biochar-assisted free radicals mediated redox reactions influencing transformation of potentially toxic metals: Occurrence, formation, and environmental applications. (15th December 2022) - Rashid, Muhammad Saqib; Liu, Guijian; Yousaf, Balal; Hamid, Yasir; Rehman, Abdul; Arif, Muhammad; Ahmed, Rafay; Ashraf, Aniqa; Song, Yu
Abstract: Potentially toxic metals have become a viable threat to the ecosystem due to their carcinogenic nature. Biochar has gained substantial interest due to its redox-mediated processes and redox-active metals. Biochar has the capacity to directly adsorb the pollutants from contaminated environments through several mechanisms such as coprecipitation, complexation, ion exchange, and electrostatic interaction. Biochar's electron-mediating potential may be influenced by the cyclic transition of surface moieties and conjugated carbon structures. Thus, pyrolysis configuration, biomass material, retention time, oxygen flow, and heating time also affect biochar's redox properties. Generally, reactive oxygen species (ROS) exist as free radicals (FRs) in radical and non-radical forms, i.e., hydroxyl radical, superoxide, nitric oxide, hydrogen peroxide, and singlet oxygen. Heavy metals are involved in the production of FRs during redox-mediated reactions, which may contribute to ROS formation. This review aims to critically evaluate the redox-mediated characteristics of biochar produced from various biomass feedstocks under different pyrolysis conditions. In addition, we assessed the impact of biochar-assisted FRs redox-mediated processes on heavy metal immobilization and mobility. We also revealed new insights into the function of FRs in biochar and its potential uses for environment-friendly remediation and reducing the dependency on fossil-based materials, utilizing local residual biomass as a raw material in terms of sustainability. Graphical abstract: Image 1 Highlights: Biochar mediated redox reactions and mechanisms of ROS-FRs formation are discussed. Immobilization and reduction mechanisms of heavy metals by biochar are reviewed. Biochar redox potential is affected by porosity, pyrolysis, and feedstock material. Heavy metals occurrence, transformation, and environmental effects are elucidated. Future perspectives for sustainable use of biochar are also suggested.